What do the Hospitality Student Find Important about Internship During the Covid 19? - Windawaty, Herry (Rumah Jurnal UNEJ, 2022)
The COVID-19 pandemic is currently sweeping the world and hitting all sectors of the economy. There are more than 3,900,000 positive cases of corona virus infection worldwide and more than 270,000 people have died. The impact of this pandemic is not only on the world of health, but also affects all aspects of people's lives. Currently, people are encouraged to do Social Distancing, where teaching and learning activities, work and worship are done at home. In addition, recommendations regarding Health protocols from WHO (World Health Organization) such as diligently washing hands, maintaining health and hygiene and always wearing masks when traveling out. This certainly has an impact on the general economic condition of the community, where many people are laid off because the company, they work for has stopped operating either temporarily or permanently. One of the sectors that has the most impact in this pandemic is the tourism sector, which includes tourist accommodation or hospitality. The hotel sector has been paralyzed in recent years. This can be seen from the decline in room occupancy rates in hotels. This study aims to see How Importance the Internship program for Podomoro University Students during the Covid 19 Pandemic. This research uses descriptive qualitative. Primary data was obtained through interviews and surveys, while secondary data was obtained from related journals, public information and previous research.